Ayurvedic management of Carpal Tunnel Syndrome with Agnikarma – A Case Report - Padadharia, Dhruval; Patel, Jigna; Sharma, Varsha; Parmar, Damini (Asian Journal of Pharmaceutical Research and Development, 2023)
Carpal tunnel syndrome is an entrapment neuropathy caused by compression of median nerve as it passes through the carpal tunnel i.e., the space between the carpal bones posteriorly and the flexor retinaculum anteriorly. The compression can be caused by skeletal abnormalities, swelling of other tissues within the tunnel or thickness of the retinaculum. The condition is common in middle aged women at the menopause. In younger patients the cause may be rheumatoid disease, pregnancy or tenosynovitis. It is a condition that causes pain, numbness, tingling, and weakness in the hand and wrist. Carpal tunnel syndrome has fast growing annual incidence rate of 5 to 50 per Ten thousand populations. Modern treatment for this condition includes injecting hydrocortisone into flexor sheaths at the carpal tunnel, wearing cock-up splint and longitudinal division of the flexor retinaculum. On the basis of structures involved and features of carpal tunnel syndrome this condition can be correlated with Snayugata Vata Vikara which affects tendons ligaments and nerve. Sushruta has advised Agnikarma for disorders of snayu (ligaments and tendons), asthi (bone), siddhi (joints) etc. Hence, in this study a case of carpel tunnel syndrome (snayugatavata) was treated by Agnikarma, along with administration of Navajivana Rasa orally, for a period of 04 weeks. This combination therapy provided considerable relief in pain and tingling sensation of wrist.